The Solution of the Intuitionistic Fuzzy Linear Fractional Partial Differential Equations Using the Homotopy Analysis Method - SADIKI, Hamid; Khadija Oufkir; M'hamed Elomari; Idris Bakhadach (International Journal of Engineering and Technology, 2024)
The present work is devoted to using an analytic approach, namely the homotopy analysis method, to solve the Fractional Partial Differential Equations with intuitionistic fuzzy initial data under generalized intuitionistic fuzzy Caputo derivative.